Synthesis and mesomorphic behavior of liquid crystal chalconyl esters. (2nd July 2016) - Jain, B. B.; Patel, R. B.
ABSTRACT: A chalconyl homologous novel series of thermotropic liquid crystals (LC) have been synthesized and studied with a view to understand and establish the effects of molecular structure on LC properties in thermotropic behaviors. Homologous series consists of 13 homologs (C1 –C18 ), C1 –C4 homologs are nonliquid crystals and the rest of the homologs are enantiotropically nematogenic without exhibition of smectic property. Transition temperatures and the textures of the nematic phase were determined by an optical polarizing microscopy, equipped with a heating stage (POM) . Texture of a nematic phase are threaded or Schlieren. The Spectral and analytical data confirms the molecular structures of homologs. Cr-N/I and N-I transition curves behaved in normal manner except C7 homolog which shows negligible abnormality for N-I transition temperature or curve with exhibition of odd-even effect.